Health Vulnerabilities and Resilience to Climate Change: An Update of International Progress - Mohd Arifuzzaman, -; Rahman, M Mizanur; Islam, Md Sultan Ul; Uddin, Md Nezam (Ibrahim Cardiac Medical Journal, 2020)
Despite being one of the most important societal challenges of the 21st century, public engagement with climate change currently remains low worldwide. Mounting evidence from across the behavioral sciences has found that most people regard climate change as a non-urgent and psychologically distant risk—spatially, temporally, and socially-which has led to deferred public decision making about mitigation and adaptation responses. Climate change is increasing risks to human health and to the health systems that seek to protect the safety and well-being of populations. Health authorities require information about current associations between health outcomes and weather or climate, vulnerable populations, projections of future risks and adaptation opportunities in order to reduce exposures, empower individuals to take needed protective actions and build climate-resilient health systems. Health authorities from local to national levels badly seek this information by conducting climate change and health vulnerability and adaptation assessments. While assessments can provide valuable information to plan for climate change impacts, they are often not integrated into adaptation decision making, probably because the health sector is not involved in climate change policy-making processes at the national level. Significant barriers related to data accessibility, a limited number of climate and health models, uncertainty in climate projections, and a lack of funding and expertise, particularly in developing countries, challenge health authority efforts to conduct rigorous assessments and apply the findings. This paper reviews the evolution of climate change and health vulnerability and adaptation assessments, including guidance developed from such projects, and implementation of the findings to support health adaptation action. The findings derived from the study will support collaborative efforts to protect health from current and future climate change hazards. Health authorities may benefit from additional resources to ensure that evidence about climate change impacts on health could effectively be translated into needed actions to build health resilience. Ibrahim Card Med J 2019; 9 (1&2): 80-92